2019
DOI: 10.1038/s41598-019-38935-7
|View full text |Cite
|
Sign up to set email alerts
|

The application of Lempel-Ziv and Titchener complexity analysis for equine telemetric electrocardiographic recordings

Abstract: The analysis of equine electrocardiographic (ECG) recordings is complicated by the absence of agreed abnormality classification criteria. We explore the applicability of several complexity analysis methods for characterization of non-linear aspects of electrocardiographic recordings. We here show that complexity estimates provided by Lempel-Ziv ’76, Titchener’s T-complexity and Lempel-Ziv ’78 analysis of ECG recordings of healthy Thoroughbred horses are highly dependent on the duration of analysed ECG fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Such error might also be limited by using algorithms which are capable of more complete parsing of the source data, as proposed by Titchener, for example 31 . In our previous work 13 we demonstrated that the behaviour of a Titchener complexity estimator in ECG analysis produced result very similar to LZ76, while the LZ78 estimator produced different results from either LZ76 and Titchener ones. We also estimated that analysis of 60-sec ECG strips might be a reasonable compromise between the competing requirements of having a sufficient amount of data with a low coefficient of variation, whilst keeping the strip length short enough to keep the observed parameters stationary during data collection.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Such error might also be limited by using algorithms which are capable of more complete parsing of the source data, as proposed by Titchener, for example 31 . In our previous work 13 we demonstrated that the behaviour of a Titchener complexity estimator in ECG analysis produced result very similar to LZ76, while the LZ78 estimator produced different results from either LZ76 and Titchener ones. We also estimated that analysis of 60-sec ECG strips might be a reasonable compromise between the competing requirements of having a sufficient amount of data with a low coefficient of variation, whilst keeping the strip length short enough to keep the observed parameters stationary during data collection.…”
mentioning
confidence: 84%
“…For the control group were used recordings from 82 healthy horses not displaying clinically significant cardiac abnormalities on prior routine cardiovascular examination. This control cohort was previously used to evaluate the feasibility of complexity analysis of equine ECG 13 . The PAF group consisted of newly recruited 10 horses for which a diagnosis of PAF had been made previously by ECG recording.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of nonlinearity, some quantitative indicators including Lyapunov exponents [31], correlation dimension [32], entropy [33], and complexity [34] have been well applied. Among of them, the Lempel-Ziv complexity (LZC) has many good advantages to measure the time series arose from the nonlinear dynamics system, which have been used widely in data compression [35], coding [36], generation of test signals [37], and so on. Additionally, compared with the methods of spectral analysis and time-frequency analysis, the LZC method can detect the long-range correlations embedded in the seemingly nonstationary time series and also avoid the spurious detection of apparent long-range correlations that are an artifact of nonstationarity [38].…”
Section: Introductionmentioning
confidence: 99%